2021
DOI: 10.1101/2021.09.11.21263419
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics and outcomes of an international cohort of 400,000 hospitalised patients with Covid-19

Abstract: Background: Policymakers need robust data to respond to the COVID-19 pandemic. We describe demographic features, treatments and clinical outcomes in the International Severe Acute Respiratory and emerging Infection Consortium (ISARIC) COVID-19 cohort, the world's largest international, standardised cohort of hospitalised patients. Methods: The dataset analysed includes COVID-19 patients hospitalised between January 2020 and May 2021. We investigated how symptoms on admission, comorbidities, risk factors, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 29 publications
3
19
2
Order By: Relevance
“…At the same time, clinical practice has rapidly advanced with growing experience and the publication of several key trials. 1 , 2 , 3 The impact of these changes on patients admitted to intensive care units (ICUs) in Australia has not been examined in detail.…”
mentioning
confidence: 99%
“…At the same time, clinical practice has rapidly advanced with growing experience and the publication of several key trials. 1 , 2 , 3 The impact of these changes on patients admitted to intensive care units (ICUs) in Australia has not been examined in detail.…”
mentioning
confidence: 99%
“…The distribution of symptoms within our cohort was similar to that of other cohorts with the most common symptoms at presentation including cough, shortness of breath, fever, headache, and chest pain. 13,42,[45][46][47][48] Of note is the gradual change in the proportion of patients presenting with fever, which decreased from 82% during the first wave to 24% during the fourth wave, in line with other contexts. 49 One large multicenter retrospective analysis on 21,461 unvaccinated Spanish COVID patients for example found that while fever was reported by 70-74% of patients during waves 1 and 2, this number decreased to 58.3% in successive waves.…”
Section: Multivariable Survival Analysismentioning
confidence: 62%
“…One large-scale multicenter observational study including almost half a million hospitalized COVID-19 patients from 49 different countries for example, showed a mortality of 20%. 45 A further multicenter observational study conducted in the United Kingdom with over 20.000 hospitalized COVID-19 patients, documented a mortality rate of 32%. 46…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations